Anatomy of Writing for Publication for Nurses, 3rd Ed. 2017 – Cynthia Saver - Clendinneng, Debra (Operating Room Nurses Association of Canada Journal, 2018)
Anatomy of Writing for Publication for Nurses, Third Edition, is a described by the author as a comprehensive yet practical guide to professional healthcare writing for nurses. The book’s goal is to demystify the writing process for those who need to bridge the gap from sentence structure to a published manuscript. The author assures readers that all nurses can learn to write effectively and enjoy the process.